Cultivating Resilience: Climate Change Adaptation in the Myanmar Central Dry Zone - International Institute of Rural Reconstruction (2023)
The "Cultivating Resilience: Climate Change Adaptation in the Myanmar Central Dry Zone" video showcases the resilience of farmers in Myanmar's central dry zone. The visual narrative demonstrates how agroforestry and small livestock-related climate adaptation initiatives are yielding notable short- and medium-term effects at the community level.